1994
DOI: 10.1038/bjc.1994.31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of glutathione S-transferase Pi in non-invasive ductal carcinoma of breast

Abstract: Summary Glutathione S-transferase Pi (GST P) has been reported to be a marker of dysplastic lesions. For this reason expression of GST P by intraduct breast carcinoma was evaluated by immunohistochemistry. Thirty-seven of 92 carcinomas (40%) were GST P positive. GST P staining did not correlate with histological variables, c-erbB-2 overexpression or with clinical outcome. The GST P status of recurrences did not correlate with that of the index lesion. There is little evidence that GST P is a useful marker of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(20 reference statements)
1
3
1
Order By: Relevance
“…Loss of GSTP1 expression was observed in 49.0% of DCIS and in 17.7% of UDH. The data of GSTP1 immunohistochemistry in DCIS are consistent with previous report [3]. Promoter hypermethylation and loss of GSTP1 expression in DCIS and UDH provide opportunities for breast cancer prevention strategies including restoration of GSTP1 function via treatment with inhibition of promoter methylation.…”
Section: Discussionsupporting
confidence: 92%
“…Loss of GSTP1 expression was observed in 49.0% of DCIS and in 17.7% of UDH. The data of GSTP1 immunohistochemistry in DCIS are consistent with previous report [3]. Promoter hypermethylation and loss of GSTP1 expression in DCIS and UDH provide opportunities for breast cancer prevention strategies including restoration of GSTP1 function via treatment with inhibition of promoter methylation.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the increased GSTP1 expression is associated with a poor prognosis [10] but conflicting results have also been reported [23]. We have also failed to demonstrate a significant association between GSTP1 expression and patient prognosis in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…11 Epigenetic silencing of the GSTP1 gene mediated by promoter hypermethylation and subsequent loss of protein expression 12 has been reported in many human cancers like human neoplasia, 13 prostate cancer, 14 and breast cancer. 15 Hypermethylation of the CpG dinucleotide in the GSTP1 promoter has further been associated with aggressive phenotype 16 and poor prognosis. 17…”
Section: Introductionmentioning
confidence: 99%